2003
DOI: 10.1097/01.ccm.0000064743.44696.49
|View full text |Cite
|
Sign up to set email alerts
|

Do-not-resuscitate order after 25 years*

Abstract: After 25 yrs of DNR orders, it remains reasonable to presume consent and attempt resuscitation for people who suffer an unexpected cardiopulmonary arrest or for whom resuscitation may have physiologic effect and for whom no information is available at the time as to their wishes (or those of their surrogate). However, it is not reasonable to continue to rely on such a presumption without promptly and actively seeking to clarify the patient's (or surrogate's) wishes. The DNR order, then, remains an inducement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 47 publications
1
105
0
9
Order By: Relevance
“…Many medically ill patients support euthanasia 30,31 , but this remains a controversial subject among physicians 32 . DNR orders are legally and ethically acceptable 33,34 , and should not be confused or conflated with euthanasia or physician assisted suicide. Physicians who are faced with an apparently illogical request for FC should explore concerns about euthanasia.…”
Section: Discussionmentioning
confidence: 99%
“…Many medically ill patients support euthanasia 30,31 , but this remains a controversial subject among physicians 32 . DNR orders are legally and ethically acceptable 33,34 , and should not be confused or conflated with euthanasia or physician assisted suicide. Physicians who are faced with an apparently illogical request for FC should explore concerns about euthanasia.…”
Section: Discussionmentioning
confidence: 99%
“…In patients whose prognoses are so poor that they are not expected to derive benefit from cardiopulmonary resuscitation, or in patients whose values and preferences are against aggressive resuscitation, DNR order sallow caretakers to potentially reduce patient suffering, comply with patient wishes, and rationalize the delivery of healthcare. 5 As such, understanding the factors that influence DNR orders and making their implementation more effective has the potential to improve the care of criticallyill patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, the patterns of DNR orders suggested that physi-cian-and institution-related biases had a stronger influence on the timing and selection of patients for DNR orders than patientrelated factors such as the presence of advance directives. 18,19 Although problems with DNR orders have been discussed for decades, substantial efforts at reform proved inadequate. Fortunately, the recent health care reform has created a national impetus to promote safe, high quality care and eliminate costly, ineffective treatments.…”
Section: Introductionmentioning
confidence: 99%